PINATUBO ERUPTION EFFECT OBSERVED AT SYOWA STATION, EAST ANTARCTICA - カネト, ススム; KANETO, Susumu (National Institute of Polar Research, 1997)
P(論文) The direct and indirect effects on solar radiation, temperature and ozone due to volcanic eruptions of Mt. Pinatubo and Mt. Hudson in 1991 were analyzed based on radiation and meteorological observations at Syowa Station (69°S, 40°E), east Antarctica. The direct effect is seen in solar radiation components. The normal incident solar radiation was decreased as much as 30% of normal value in December 1991,while the diffuse solar radiation increased 50%. In December 1992,the decrease of normal incident radiation fell 20% and the increase of diffuse radiation fell 30%. The indirect effect is thought to appear in atmospheric temperature and stratospheric ozone. At the altitudes where volcanic aerosol is injected, atmospheric temperature will be raised and at the altitudes below that, the temperature will drop. From Syowa station aerological data, there was little temperature increase in the lower stratosphere 6 months after the eruptions. The annual mean surface temperature of Syowa in 1991 and 1992 was both -9.9℃, in 1993 it became -11.8℃. The annual mean value of total ozone observed at Syowa in 1993 was almost the same as in the previous few years, but in 1994,it recorded its lowest value. From Syowa Station data, the direct effect of the eruptions on solar radiation components appeared quickly, within 6 months, and the magnitude was almost the same as shown by global observations. The indirect effect on atmospheric temperature or total ozone seems to be weakened or postponed compared to the global appearance. departmental bulletin paper